FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENCEGAHAN PENYAKIT INFEKSI MENULAR SEKSUAL (IMS) PADA PEKERJA SOPIR ANGKUTAN UMUM JALUR “H” DIKOTA SORONG - Fikram Maswatu; S.L Momot; Jansen Parlaungan (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2018)
Sexually Transmitted Infections (STIs) are infectious or infectious diseases that are transmitted through sexual contact from the penis, vagina, anal and oral. Preliminary study at the City Health Office of Sorong, the number of data on cases of Sexually Transmitted Infections (STIs) in the last 2 years of 2016-2017 was 122 people consisting of 19 men and 103 women. Objective: To find out the factors related to the prevention of sexually transmitted infections (STIs) in public transport drivers in the